Characterizing Linear Mappings Through Unital Algebra - Atteya, Mehsin Jabel (Universitas Brawijaya, 2025)
In this paper, we characterize the two linear mappings σ and τ satisfying the identity, x ° y^=0 yields σ(x)° y^+x° τ(y)^=0 for all x, y A, where A is an -algebra over a real or complex field K from a unital algebra into its unital -bimodule. Moreover, we push a complete description of linear mapping that σ is a linear mapping from A into M satisfying X, Y A, X ° Y=0 yields σ(X)° Y-X° σ(Y)=0 and each element of A has a weak inverse.